A modified phenolic resin-based hard carbon material applied to a sodium ion battery, a preparation method thereof and a sodium ion battery negative electrode material
Patent Information
- Application Number
- CN202610301108.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-12
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-03-12
AI Technical Summary
[0005]本发明的目的在于提出一种应用于钠离子电池的改性酚醛树脂基硬碳材料及其制备方法和钠离子电池负极材料,以解决现有技术中硬碳材料首次库仑效率低、压实密度不足、循环寿命短、制备成本高的技术问题
[0027]1、通过壳聚糖的原位氮掺杂优化了材料的电子结构,减少了不可逆容量损失,氧化铁催化促进了石墨化,降低了缺陷密度,碳包覆层修复了表面缺陷,减少了SEI膜的形成。
Smart Images

Figure CN122059396B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a modified phenolic resin-based hard carbon material for sodium-ion batteries, its preparation method, and a sodium-ion battery anode material. Background Technology
[0002] With the transformation of the global energy structure and the rapid development of renewable energy, electrochemical energy storage technology is playing an increasingly important role in the energy system. Lithium-ion batteries, as the most mature electrochemical energy storage technology currently available, have been widely used in portable electronic devices, electric vehicles, and energy storage power stations. However, the uneven distribution of lithium resources, limited reserves, and rising costs severely restrict the further development of lithium-ion batteries in large-scale energy storage.
[0003] Carbon-based materials are abundant, structurally tunable, have low operating potentials, and long cycle lives, making them among the most promising anode materials. In recent years, hard carbon has been considered a promising anode material for sodium-ion batteries due to its large interlayer spacing, good structural stability, and high reversible capacity; however, hard carbon suffers from low initial coulombic efficiency. Studies have found that hard carbon prepared from the pyrolysis of materials such as phenolic resins, furfural, and pitch exhibits good initial efficiency and cycle life, but its reversible specific capacity is only 180-260 mAh / g, corresponding to low energy density in sodium-ion batteries. Existing resin-based hard carbon materials, due to their poor reversible specific capacity and cycle performance, limit their further development in the field of sodium-ion battery anodes.
[0004] Chinese invention patent document CN121426083A discloses a nitrogen-doped hard carbon anode material and its preparation method, which solves the problem of low initial coulombic efficiency of existing hard carbon materials. The prepared product has good conductivity and high activity, and can be used in lithium-ion batteries with high capacity. The obtained material has the following main characteristics: 1. High specific capacity, 190-260 mAh / g; 2. Initial coulombic efficiency >80%. Although the conductivity is improved by introducing nitrogen, its effect on improving the initial coulombic efficiency is limited. Summary of the Invention
[0005] The purpose of this invention is to propose a modified phenolic resin-based hard carbon material for sodium-ion batteries, its preparation method, and a sodium-ion battery anode material, so as to solve the technical problems of low initial coulombic efficiency, insufficient compaction density, short cycle life, and high preparation cost of existing hard carbon materials.
[0006] The technical solution of this invention is implemented as follows:
[0007] This invention provides a modified phenolic resin-based hard carbon material for use in sodium-ion batteries, comprising the following raw materials in parts by weight: 5-20 parts chitosan, 8-15 parts cyclohexamethylenetetramine, 10-12 parts resorcinol, 10-15 parts citrate, and 3-5 parts coating agent.
[0008] As a further improvement of the present invention, the citrate comprises magnesium citrate and iron citrate in a mass ratio of 3-5:8; the coating agent is selected from at least one of sucrose, glucose, and polyvinyl alcohol.
[0009] Preferably, the hard carbon material has a hierarchical porous structure, including a three-level pore system of micropores, mesopores, and macropores.
[0010] This invention further protects a method for preparing the above-mentioned modified phenolic resin-based hard carbon material for sodium-ion batteries, comprising the following steps:
[0011] S1. Chitosan, cyclohexamethylenetetramine, and resorcinol are added to a mixed solvent, stirred and mixed, subjected to hydrothermal reaction, filtered, washed, and dried to obtain a chitosan-modified phenolic resin precursor.
[0012] Chitosan participates in the polymerization reaction of phenolic resins, forming an interpenetrating double network structure, thereby achieving in-situ nitrogen doping. This allows for the formation of various nitrogen species, such as pyrrole nitrogen and graphitic nitrogen, improving the material's electronic conductivity and surface wettability, while providing more active sites for sodium ion storage. Compared to traditional methods of adding nitrogen-containing substances, the in-situ nitrogen generated by chitosan is uniformly dispersed in the system, avoiding microcrystalline structure distortion or stress concentration caused by excessively high local nitrogen concentrations in traditional methods. This improves the material's structural integrity and cycle stability. Furthermore, the chitosan polysaccharide framework supports the cross-linked network of the phenolic resin in the early stages of carbonization, preventing softening and flow, ensuring the final hard carbon material has a porous morphology and preventing pore collapse.
[0013] S2. Chitosan-modified phenolic resin precursor and citrate are added to water, stirred and mixed, alkaline solution is added, heated and stirred to react, dried, carbonized in two stages, acid washed, and washed with water until neutral to obtain a hard carbon matrix.
[0014] This invention utilizes citrates, including magnesium citrate and iron citrate. During the carbonization process of citrates, metal oxides (iron oxide and magnesium oxide) and carbon materials are formed. Iron oxide promotes the graphitization of the carbon materials and regulates the interlayer spacing during high-temperature carbonization. Magnesium oxide and residual alkali oxides (NaOH, KOH) activate pore formation. Simultaneously, the carbon materials decompose during high-temperature carbonization, generating gases and forming abundant channels and a unique hierarchical porous structure. Due to the high porosity, hierarchical pore structure, and abundant oxygen atoms on the surface of the hierarchical porous carbon materials, they exhibit high specific capacitance, excellent rate performance, and cycling stability. The metal oxides are subsequently washed with hydrochloric acid to reduce the doping of other impurities.
[0015] S3. The hard carbon matrix is mixed with the coating agent solution, dried, and then heat-treated under an inert atmosphere to obtain a modified phenolic resin-based hard carbon material for use in sodium-ion batteries.
[0016] Carbon coating can repair defects on the material surface, reduce the formation of SEI film during the first charge and discharge, and improve the first coulombic efficiency; at the same time, carbon coating can enhance the structural stability of the material and extend the cycle life.
[0017] Preferably, the inert atmosphere is nitrogen, argon, or a mixture of both, with a gas flow rate of 50-500 mL / min and an oxygen content of less than 10 ppm.
[0018] As a further improvement of the present invention, the temperature of the hydrothermal reaction in step S1 is 160-180°C and the time is 20-28h.
[0019] As a further improvement of the present invention, the alkaline solution in step S2 is a 2-3 mol / L NaOH or KOH solution, and the heating and stirring reaction temperature is 60-80℃, and the time is 1-3 h.
[0020] As a further improvement of the present invention, the two-stage carbonization in step S2 includes a first stage and a second stage. The conditions for the first stage are: heating to 600-900℃ at a heating rate of 2-5℃ / min and holding at that temperature for 1-4 hours; the conditions for the second stage are: heating to 1200-1500℃ at a heating rate of 10-15℃ / min under an inert gas atmosphere and holding at that temperature for 2-6 hours. The first stage is a low-temperature carbonization stage, in which the pyrolysis and volatilization of organic matter mainly occur, forming a preliminary carbon skeleton structure. In the second stage, a high-temperature carbonization stage, under the promotion of iron oxide, the carbon material undergoes rearrangement and graphitization, forming a layered structure suitable for sodium ion insertion.
[0021] As a further improvement of the present invention, the heat treatment conditions in step S3 are 800-1000℃ and held for 1-3 hours.
[0022] As a further improvement of the present invention, the preparation method further includes step S4, pulverization and classification: the surface-modified phenolic resin-based hard carbon material for sodium-ion batteries is subjected to air jet pulverization and classification to obtain a finished product with a particle size D50 of 5-15 μm. A suitable particle size distribution is beneficial to improving the compaction density and electrochemical performance of the material.
[0023] This invention further protects a sodium-ion battery anode material, which uses the modified phenolic resin-based hard carbon material used in sodium-ion batteries as the active material. The anode material is prepared from the following raw materials in parts by weight: 90-98 parts of active material, 1-5 parts of conductive agent, and 1-5 parts of binder.
[0024] Preferably, the conductive agent is conductive carbon black super-P; the binder is polyvinylidene fluoride (PVDF).
[0025] As a further improvement of the present invention, the sodium-ion battery has an initial coulombic efficiency of 88-92%, an initial reversible sodium storage capacity of 370-400 mAh / g, and a capacity retention rate of more than 93% after 300 cycles at a 0.1C rate.
[0026] The present invention has the following beneficial effects:
[0027] 1. In-situ nitrogen doping of chitosan optimized the electronic structure of the material, reducing irreversible capacity loss. Iron oxide catalyzed and promoted graphitization, reducing defect density. The carbon coating repaired surface defects and reduced the formation of SEI film.
[0028] 2. The compaction density of the hard carbon material of the present invention is higher than that of traditional hard carbon materials. This is due to the appropriate particle size distribution and the lubricating effect of the surface carbon coating layer, which enables the material particles to be tightly packed, thereby improving the volumetric energy density of the electrode.
[0029] 3. The hard carbon material of this invention has a significantly longer cycle life than traditional hard carbon materials. The hierarchical porous structure provides a buffer space for the insertion / extraction of sodium ions, reducing volume expansion. The carbon coating layer protects the active material from direct contact with the electrolyte and suppresses side reactions.
[0030] 4. This invention uses phenolic resin and chitosan as the main raw materials, which are widely available and inexpensive; the preparation process is simple and easy to scale up for industrial production. Compared with hard carbon materials that use expensive template agents or complex processes, the production cost of this invention is reduced. Attached Figure Description
[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 The image shows the SEM image of the hard carbon matrix obtained in step S2 of Example 1.
[0033] Figure 2 The infrared spectrum is shown for the modified phenolic resin-based hard carbon material prepared in Example 1 for use in sodium-ion batteries. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] In this embodiment, the inert atmosphere used is nitrogen, the gas flow rate is 100 mL / min, and the oxygen content in the atmosphere is less than 10 ppm.
[0036] Example 1
[0037] This embodiment provides a method for preparing a modified phenolic resin-based hard carbon material for use in sodium-ion batteries, comprising the following steps:
[0038] S1. Add 10g chitosan, 8g cyclohexamethylenetetramine and 10g resorcinol to 1L of acetic acid solution with a concentration of 2wt%, stir and mix for 30min, hydrothermally react at 170℃ for 24h, filter, wash and dry to obtain chitosan modified phenolic resin precursor.
[0039] S2. Add the chitosan-modified phenolic resin precursor obtained in step S1 and 10g of citrate to 500mL of water, stir and mix, add 100mL of 2mol / L NaOH solution, heat to 70℃, stir and react for 2h, dry, carbonize in two stages under an inert gas atmosphere, wash with 10wt% hydrochloric acid, and wash with water until neutral to obtain a hard carbon matrix. Figure 1 The image shows a SEM image of the hard carbon matrix, which reveals a multi-level porous structure. The citrate consists of magnesium citrate and iron citrate in a mass ratio of 3:8.
[0040] The two-stage carbonization includes a first stage and a second stage. The conditions for the first stage are: heating to 750°C at a heating rate of 3°C / min and holding at that temperature for 2 hours; and the conditions for the second stage are: heating to 1350°C at a heating rate of 12°C / min and holding at that temperature for 4 hours.
[0041] S3. The hard carbon matrix obtained in step S2 is mixed evenly with 100 mL of aqueous solution containing 3 g of glucose. After drying, it is heat-treated at 900 °C for 2 h under an inert atmosphere, followed by air jet milling and classification to obtain a finished product with a particle size D50 of 10 μm. Figure 2 The infrared spectrum of the obtained product shows that the hard carbon material contains graphitic nitrogen structure, pyridine nitrogen group structure, C=C double bond group structure, OH group structure, COC group structure and CC group structure.
[0042] Example 2
[0043] This embodiment provides a method for preparing a modified phenolic resin-based hard carbon material for use in sodium-ion batteries, comprising the following steps:
[0044] S1. Add 12g chitosan, 15g cyclohexamethylenetetramine and 12g resorcinol to 1L of acetic acid solution with a concentration of 2wt%, stir and mix for 30min, hydrothermally react at 170℃ for 24h, filter, wash and dry to obtain chitosan modified phenolic resin precursor.
[0045] S2. Add the chitosan-modified phenolic resin precursor obtained in step S1 and 15g of citrate to 500mL of water, stir and mix, add 100mL of 3mol / L KOH solution, heat to 70℃, stir and react for 2h, dry, carbonize in two stages under an inert atmosphere, wash with 10wt% hydrochloric acid, and wash with water until neutral to obtain a hard carbon matrix; the citrate includes magnesium citrate and iron citrate in a mass ratio of 5:8;
[0046] The two-stage carbonization includes a first stage and a second stage. The conditions for the first stage are: heating to 750°C at a heating rate of 3°C / min and holding at that temperature for 2 hours; and the conditions for the second stage are: heating to 1350°C at a heating rate of 12°C / min and holding at that temperature for 4 hours.
[0047] S3. The hard carbon matrix obtained in step S2 is mixed evenly with 100 mL of aqueous solution containing 5 g of sucrose. After drying, it is heat-treated at 900 °C for 2 h under an inert atmosphere, followed by air jet milling and classification to obtain a finished product with a particle size D50 of 10 μm.
[0048] Example 3
[0049] This embodiment provides a method for preparing a modified phenolic resin-based hard carbon material for use in sodium-ion batteries, comprising the following steps:
[0050] S1. Add 11g chitosan, 10g cyclohexamethylenetetramine and 11g resorcinol to 1L of acetic acid solution with a concentration of 2wt%, stir and mix for 30min, hydrothermally react at 170℃ for 24h, filter, wash and dry to obtain chitosan modified phenolic resin precursor.
[0051] S2. Add the chitosan-modified phenolic resin precursor obtained in step S1 and 12g of citrate to 500mL of water, stir and mix, add 100mL of 2.5mol / L NaOH solution, heat to 70℃, stir and react for 2h, dry, carbonize in two stages under an inert atmosphere, wash with 10wt% hydrochloric acid, wash with water until neutral, and obtain a hard carbon matrix; the citrate includes magnesium citrate and iron citrate in a mass ratio of 4:8;
[0052] The two-stage carbonization includes a first stage and a second stage. The conditions for the first stage are: heating to 750°C at a heating rate of 3°C / min and holding at that temperature for 2 hours; and the conditions for the second stage are: heating to 1350°C at a heating rate of 12°C / min and holding at that temperature for 4 hours.
[0053] S3. The hard carbon matrix obtained in step S2 is mixed evenly with 100 mL of aqueous solution containing 4 g of glucose. After drying, it is heat-treated at 900 °C for 2 h under an inert atmosphere, followed by air jet milling and classification to obtain a finished product with a particle size D50 of 10 μm.
[0054] Example 4
[0055] The only difference from Example 3 is that the citrate is a single magnesium citrate.
[0056] Example 5
[0057] The only difference from Example 3 is that the citrate is a single iron citrate.
[0058] Comparative Example 1
[0059] The only difference from Example 3 is that chitosan is replaced by dopamine hydrochloride in step S1.
[0060] Comparative Example 2
[0061] The only difference from Example 3 is that step S1 is different, and in step S2, the chitosan-modified phenolic resin precursor is replaced by an equal mass of a mixture. Step S1 is as follows:
[0062] Add 100g of thermosetting phenolic resin (molecular weight 2000, softening point 95℃, residual carbon rate 48%) and 10g of urea to a high-speed mixer and mix at 1000rpm for 30 minutes to obtain a mixture.
[0063] Comparative Example 3
[0064] The only difference from Example 3 is that citrate was not added in step S2. Step S2 is as follows:
[0065] The chitosan-modified phenolic resin precursor obtained in step S1 was carbonized in two stages under an inert gas atmosphere and then washed to obtain a hard carbon matrix.
[0066] The two-stage carbonization includes a first stage and a second stage. The conditions for the first stage are: heating to 750°C at a heating rate of 3°C / min and holding at that temperature for 2 hours; and the conditions for the second stage are: heating to 1350°C at a heating rate of 12°C / min and holding at that temperature for 4 hours.
[0067] Comparative Example 4
[0068] The only difference from Example 3 is that the two-stage carbonization was replaced by heating to 1350°C at a heating rate of 12°C / min and holding for 4 hours.
[0069] Comparative Example 5
[0070] The only difference from Example 3 is that glucose coating was not added in step S3. Step S3 is as follows:
[0071] The hard carbon matrix obtained in step S2 is subjected to air jet milling and classification to obtain a finished product with a particle size D50 of 10 μm.
[0072] Example 6
[0073] This embodiment provides a sodium-ion battery negative electrode material, using the modified phenolic resin-based hard carbon material for sodium-ion batteries prepared in Example 1 as the active material. The active material content is 92 wt%, the conductive agent content is 4 wt%, and the binder content is 4 wt%. After mixing and preparing the components into a slurry, the slurry is coated onto a current collector aluminum foil, dried, pressed under a pressure of 1 MPa, and then stamped to prepare a negative electrode sheet.
[0074] Examples 7-10 and Comparative Examples 6-10
[0075] The only difference from Example 6 is that the modified phenolic resin-based hard carbon material used in sodium-ion batteries was prepared from Examples 2-5 or Comparative Examples 1-5.
[0076] Test Example 2
[0077] Using the negative electrode sheets prepared in Examples 6-10 and Comparative Examples 6-10 as negative electrodes, respectively, and using metallic sodium as the counter electrode, and 1 mol / L NaPF6 or NaClO4 as the electrolyte, sodium-ion batteries were fabricated after processes such as electrolyte injection and encapsulation.
[0078] The first reversible sodium storage capacity and the first coulombic efficiency were tested at 0.1C rate under conditions of 25°C. After 300 cycles at 0.1C rate, the reversible sodium storage capacity was measured and the capacity retention was calculated.
[0079] The method for first reversible sodium storage capacity test at 0.1C rate is as follows: charge and discharge test is performed at a current density of 0.1C, with a discharge cutoff voltage of 0V and a charging cutoff voltage of 2.8V.
[0080] The results are shown in Table 1.
[0081] Table 1
[0082] Group 0.1C First Reversible Sodium Storage Capacity (mAh / g) First-time coulomb efficiency (%) Capacity retention rate (%) after 300 cycles Example 1 348.6 89.7 94.2 Example 2 342.2 90.2 93.9 Example 3 346.7 91.0 95.6 Example 4 312.6 83.2 89.3 Example 5 320.3 86.3 91.7 Comparative Example 1 283.8 80.2 84.5 Comparative Example 2 253.6 72.6 80.4 Comparative Example 3 291.4 81.0 86.2 Comparative Example 4 304.5 82.1 87.6 Comparative Example 5 318.8 84.6 88.3
[0083] As can be seen from the table above, the sodium-ion batteries prepared from the negative electrode sheets obtained in Examples 6-8 of this invention have better overall performance.
[0084] In Example 4, citrate was a single magnesium citrate, and in Example 5, citrate was a single ferric citrate. Comparative Example 3 did not add citrate, resulting in decreased electrochemical performance. This invention, by adding citrate, including magnesium citrate and ferric citrate, forms metal oxides (iron oxide and magnesium oxide) and carbon materials during the carbonization process. Iron oxide promotes graphitization of the carbon materials and regulates interlayer spacing during high-temperature carbonization. Magnesium oxide and residual alkali oxides (NaOH, KOH) activate pore formation. Simultaneously, the carbon materials decompose during high-temperature carbonization, generating gas and forming abundant channels and a unique hierarchical porous structure. Due to the high porosity, hierarchical pore structure, and abundant oxygen atoms on the surface of the hierarchical porous carbon materials, they exhibit high specific capacitance, excellent rate performance, and cycling stability. Subsequently, the metal oxides are washed with hydrochloric acid to reduce the doping of other impurities.
[0085] In Comparative Example 1, chitosan was replaced with dopamine hydrochloride. Although nitrogen was also introduced, chitosan participated in the polymerization reaction of phenolic resin to form an interpenetrating double network structure, achieving in-situ nitrogen doping. This improved the material's electronic conductivity and surface wettability, while also providing more active sites for sodium ion storage, thus enhancing the material's structural integrity and cycling stability. Furthermore, the chitosan polysaccharide framework can support the cross-linked network of phenolic resin in the early stages of carbonization, preventing its softening and flow, ensuring the final hard carbon material has a porous morphology and avoiding pore collapse.
[0086] In Comparative Example 2, the chitosan-modified phenolic resin was replaced by a mixture of phenolic resin and urea. This mixture was unevenly mixed, which may lead to microcrystalline structure distortion or stress concentration due to excessively high local nitrogen concentration, thus resulting in a decrease in performance.
[0087] In Comparative Example 4, the two-stage carbonization was replaced by a single high-temperature carbonization, which caused structural collapse and thus reduced performance. In this invention, the two-stage carbonization works synergistically. In the low-temperature carbonization stage, the pyrolysis and volatilization of organic matter mainly occur, forming a preliminary carbon skeleton structure. In the high-temperature carbonization stage, under the promotion of iron oxide, the carbon material undergoes rearrangement and graphitization, forming a layered structure suitable for sodium ion insertion.
[0088] Comparative Example 5 did not involve glucose coating. The carbon coating layer can repair defects on the material surface, reduce the formation of the SEI film during the first charge and discharge, and improve the first coulombic efficiency; at the same time, the carbon coating layer can enhance the structural stability of the material and extend the cycle life.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A modified phenolic resin-based hard carbon material for use in sodium-ion batteries, characterized in that, The raw materials include the following parts by weight: 5-20 parts chitosan, 8-15 parts cyclohexamethylenetetramine, 10-12 parts resorcinol, 10-15 parts citrate, and 3-5 parts coating agent; wherein the citrate comprises magnesium citrate and iron citrate in a mass ratio of 3-5:8; the preparation method of the hard carbon material is as follows: S1. Chitosan, cyclohexamethylenetetramine, and resorcinol are added to a mixed solvent, stirred and mixed, subjected to hydrothermal reaction, filtered, washed, and dried to obtain a chitosan-modified phenolic resin precursor. S2. Chitosan-modified phenolic resin precursor and citrate are added to water, stirred and mixed, alkali solution is added, heated and stirred to react, dried, carbonized in two stages, acid washed, and washed with water until neutral to obtain a hard carbon matrix; the two-stage carbonization includes a first stage and a second stage. The conditions for the first stage are: heating to 600-900℃ at a heating rate of 2-5℃ / min and holding for 1-4h; the conditions for the second stage are: heating to 1200-1500℃ at a heating rate of 10-15℃ / min under an inert gas atmosphere and holding for 2-6h. S3. The hard carbon matrix is mixed with the coating agent solution, dried, heat-treated under an inert atmosphere, and then subjected to air jet milling and classification to obtain a modified phenolic resin-based hard carbon material with a particle size D50 of 5-15 μm for use in sodium-ion batteries.
2. The modified phenolic resin-based hard carbon material for sodium-ion batteries according to claim 1, characterized in that, The coating agent is selected from at least one of sucrose, glucose, and polyvinyl alcohol.
3. The modified phenolic resin-based hard carbon material for sodium-ion batteries according to claim 1, characterized in that, The hydrothermal reaction in step S1 is carried out at a temperature of 160-180℃ for 20-28 hours.
4. The modified phenolic resin-based hard carbon material for sodium-ion batteries according to claim 1, characterized in that, The alkaline solution mentioned in step S2 is a 2-3 mol / L NaOH or KOH solution, and the heating and stirring reaction is carried out at a temperature of 60-80℃ for 1-3 hours.
5. The modified phenolic resin-based hard carbon material for sodium-ion batteries according to claim 1, characterized in that, The heat treatment conditions described in step S3 are 800-1000℃ and held for 1-3 hours.
6. A sodium-ion battery anode material, characterized in that, The modified phenolic resin-based hard carbon material for sodium-ion batteries according to any one of claims 1-5 is used as the active material, and the negative electrode material is prepared from the following raw materials in parts by weight: 90-98 parts of active material, 1-5 parts of conductive agent, and 1-5 parts of binder.
Citation Information
Patent Citations
Nitrogen-doped hard carbon negative electrode material and preparation method thereof
CN121426083A
Hard carbon material, preparation method and application thereof, and secondary battery
CN116534838A